STRATEGI PENGUATAN HABITUS MODERASI KEAGAMAAN MELALUI TRANSFORMASI ASWAJA BERBASIS PESANTREN: Strategy For Strengthening Religious Moderation Habitus Through Aswaja Transformation Based On Islamic Boarding School - subekti, yusuf agung; Muhammad Faishal Haq (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to identify strategies for strengthening religious identity through the transformation of Ahlussunnah wal Jamaah (Aswaja) in Islamic boarding school-based institutions. A library research method with thematic analysis of recent scholarly sources was employed. The findings reveal five key components of effective strategies: integrating Aswaja values into the syllabus, interactive and applicative learning, kyai and teacher leadership as role models, authentic evaluation based on moderation competencies, and continuous policy and teacher training support. These strategies enhance Aswaja identity awareness and foster inclusive religious engagement, enabling pesantren to remain adaptive to contemporary challenges while preserving Islamic scholarly traditions